Harnessing plant growth-promoting bacteria (Herbaspirillum seropedicae) from an optimal mineral nitrogen supply: A study on improving nitrogen use efficiency in marandu palisadegrass - Thiengo, Cássio Carlette; Galindo, Fernando Shintate [UNESP]; Rodak, Bruna Wurr; Bernardes, João Victor Silva; da Rocha, Letícia Oliveira; Gaziola, Salete Aparecida; Azevedo, Ricardo Antunes; Burak, Diego Lang; Olivares, Fábio Lopes; Lavres, José (Elsevier, 2025)
Increasing nitrogen use efficiency (NUE) remains a crucial topic in contemporary agriculture. Inoculation with endophytic diazotrophic bacteria offers a potential solution, but the results vary with the N-fertilization regime. Here, we examined the efficacy of inoculation with Herbaspirillum seropedicae strain HRC54 in enhancing NUE and promoting the growth of Marandu palisadegrass with varying levels of N-urea (0, 25, 50, and 100 mg N kg soil⁻1). We evaluated NUE indicators and conducted complementary analyses covering biochemical, physiological, nutritional and growth-related parameters after cultivating the plants within a greenhouse environment and maintaining controlled conditions of temperature and humidity. Growth promotion was evident in inoculated plants receiving up to 50 mg N kg soil−1, with enhanced root growth orchestrating the improvement in NUE. Inoculation also improved the nutritional status of the plants (increased N and P accumulation and N balance index) and increased photosynthesis-related parameters, resulting in increased biomass yield. Insufficient N supply led to oxidative stress (overproduction of H₂O₂ and MDA), which was associated with a reduction in photosystem II efficiency, chlorophyll concentration, and soluble proteins, but only in plants that did not receive microbial inoculation. Conversely, a high N supply (100 mg N kg soil−1) combined with H. seropedicae had no synergistic effect, as NUE and the associated benefits did not improve. Therefore, inoculation with H. seropedicae is effective at increasing NUE when combined with moderate N rates. These findings support a more rational use of N fertilizers to optimize inoculation benefits and enhance NUE in tropical forage crops.
Keywords: Endophytic diazotrophic bacteria; N recovery; Oxidative stress; Photosynthetic efficiency; Root growth promotion